The Evaluation of Attitude, Knowledge and Practice of Alternative Medicine - B Alkahil, Hadeel; Al-abdullah, Malak Z; Abdulbaki, Merna M; Almuqbil, Amani F; Alshammari, Hanin S; Alhussain, Fatimah M; Alhasan, Juhaina S; Alwehaibi, Nada K; Almakdob, Dalal A; Aljoiab, Nora (International Journal of Innovative Research in Medical Science, 2017)
Background: Alleviating pains and improving patient's health status are the fundamentals in practice of medicine over many years. Unfortunately, health care providers neglect the use of natural products. The side effects of the medical therapy led the people to seeks the use of alternative therapies. Objectives: This study focused on the knowledge, attitude and use of CAM among a sample of women in Riyadh practice. Methodology: An observational, cross sectional, community based, and multi-center study was conducted. After obtaining verbal consent, data were collected using a face- to-face interview based questionnaire. Results: The awareness was great among the participant and most of participants preferred to use AM in combination with conventional medicine, Most patients with diabetes, dermatological disease, headache, and tiredness don’t prefer AM for treatment, butwas commonly used in the treatment of menstrual pain. The commonest reasons for preferening CAM that they are natural products and to avoid the side effects of drugs. Most of participants had no side effects after using CAM, 97% reported improvement after using it and are willing to use it in the future. Conclusion: This study showed the advanced knowledge about CAM among study sample. More awareness in the community required from health care providers and governmental efforts in order to shed a light on the importance of CAM as a recognized treatment modality.